Implementing Village Fund Allocation: A Study of Community Empowerment in Siantar Barat, Pematangsiantar - Sam Andre Situngkir; Subhilhar Subhilhar; Marlon Sihombing (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to analyze the implementation of the Village Fund allocation and its impact on community empowerment in West Siantar District, Pematangsiantar City. The Kelurahan Fund is an important instrument in village-based development that aims to improve community welfare through various empowerment programs. However, its implementation often faces planning, management, and community participation challenges. This research uses a qualitative approach with a case study design involving in-depth interviews, Focus Group Discussions (FGDs), and documentation. The results show that while Dana Kelurahan contributes to essential infrastructure development, its impact on community empowerment is limited. Most funds are allocated for physical activities, while social and economic empowerment activities, such as skills training and micro-enterprise development, receive less attention. Community participation in the planning and management process of Dana Kelurahan is also minimal, leading to a low sense of ownership of the programs. Key challenges faced in implementing Dana Kelurahan include the limited capacity of kelurahan officials, low transparency in fund management, and a lack of ongoing support for empowerment programs. This research recommends capacity building of kelurahan officials, community empowerment in planning and evaluation, and greater transparency in the management of Dana Kelurahan to increase its effectiveness in community empowerment.